Evaluation of interactions between Rhynchosporium secalis and Pyrenophora teres on barley - Xue, A.G.; Burnett, P.A. (Phytoprotection, 1995)
Interactions between Rhynchosporiumsecalis and Pyrenophora teres were investigated on barley (Hordeum vulgare) seedlings grown in a greenhouse and growth chambers. Following mixed inoculations, the two pathogens colonized the same leaf simultaneously, but the leaf area with symptoms (LAS) was less than that produced by either of the two pathogens alone at the same inoculum concentration. On plants inoculated with the mixed inocula, LAS induced by R. secalis was reduced by a greater amount than LAS induced by P. teres. The predominance of P. teres over R. secaliswas observed even when inoculations with R. secalis either preceded or followed the inoculation with P. teres by 24 h. Antagonism occurred when inoculum densities were 103-104 spores mL-1 for each pathogen, wetting periods were 24-28 h, and incubation temperature was above 12°C.